2021
DOI: 10.1186/s12905-021-01341-1
|View full text |Cite
|
Sign up to set email alerts
|

Management of uterine cystic adenomyosis by laparoscopic surgery: case report

Abstract: Background Endometriosis of the uterine body can be manifested as diffuse solid lesions or cystic lesions. The former is common, while the latter is rare, especially for cystic adenomyosis larger than 5 cm. Case presentation A 30-year-old woman was admitted for severe and worsening dysmenorrhea. Ultrasound examination revealed a rare well-circumscribed cystic lesion about 5.5 × 4 × 5.0 cm. CA-125 level was slightly elevated. She accepted laparoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Increased serum CA125 levels have also been proposed as a diagnostic tool for cystic adenomyosis. Cucinella et al ( 5 ) and Zhao et al ( 8 ) respectively described a large adenomyotic cyst with slightly elevated CA125. Furthermore, two cases of giant adenomyotic cyst originating from the cervix with raised CA125 levels were also reported by Pontrelli et al ( 9 ) and Isik et al ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum CA125 levels have also been proposed as a diagnostic tool for cystic adenomyosis. Cucinella et al ( 5 ) and Zhao et al ( 8 ) respectively described a large adenomyotic cyst with slightly elevated CA125. Furthermore, two cases of giant adenomyotic cyst originating from the cervix with raised CA125 levels were also reported by Pontrelli et al ( 9 ) and Isik et al ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 1908, Cullen first described uterine cystic lesions filled with chocolate-colored fluid ( 4 ). As a special type of endometriosis, the incidence of uterine cystic adenomyosis is low, and related literature reports in the past 30 years are shown in Table 1 ( 5 46 ). Terms often used in the literature include juvenile cystic adenomyosis (JCA), cystic myometrial lesions, juvenile adenomyotic cysts, uterine cystic adenomyosis, adenomyotic cyst of the uterus, adenomyotic cyst, intramyometrial cystic adenomyosis, or intrauterine cystic adenomyosis.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgical resection is suitable for lesions in the myometrium, close to the serosal layer. Laparoscopic resection can significantly improve related dysmenorrhea and increase the possibility of successful pregnancy ( 39 , 46 ). Robot-assisted laparoscopic management allows an optimal view and more efficient multilayer closure of the hysterotomy, thereby increasing the safety of future pregnancies ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Takeuchi et al ( 9 ) reported that the patient's CA-125 level could be normal or >500 U/mL. The diagnostic criteria for cystic adenomyosis are as follows ( 25 ): (1) isolated lesions; (2) no abnormalities in the uterus, fallopian tubes, and ovaries; (3) post-operative lesions with pathological reports of cystic adenomyosis; (4) excised lesions with endometrial glands and interstitium; (5) lesions that contain thick chocolate-like liquid; and (6) small lesions of adenomyosis, such as adenomyoma, that can be seen in the muscle layer adjacent to the lesion.…”
Section: Discussionmentioning
confidence: 99%